Development and reliability of a framework to assess cognitive-motor function in sport - Bertozzi, F.; Monfort, S. M.; Di Giovanni, E.; Brunetti, C.; Sforza, C.; Galli, M.; Tarabini, M. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: Reduced cognitive ability may affect sports performance and increase injury risk. Current cognitive function screening tools in athletes include stationary procedures that may lack external validity, whole-body movements, and time constraints. We aimed to study the reliability and the between- and within-session variations of newly developed cognitive-motor tests.